PENERAPAN PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN KONTEKSTUAL DI KELAS X.B SMA NEGERI 1 INDRALAYA SELATAN - Wahyu Wibowo; Yusuf Hartono; Trimurti Saleh (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2016)
This research is a descriptive research that have a purpose to know description of learning math application by contextual learning approachment which is evaluated from student activity and the student study result after following math learning with contextual approachment in the X.B SMA Negeri 1 Inderalaya Selatan class. These research subjects number 25 student of X.B SMA Negeri 1 Indralaya Selatan school year 2013/2014 class. Technique of data accumulation that was done are by observation and test. The carried out data of student learning activity is collected with observation. While the test is used for knowing the student learning result after studying math by contextual approachment. As for carried out percentages of student learning activity at learning application by contextual approachment is equal to 72% that include in good category. While the percentages of efficacy student studying result mean equal to 75,48 that are categorized as a good one. So that from that assessment can be concluded that learning math application by contextual learning approachment which is evaluated from student activity and the student study result can be categorised as a good one.